Implementing generalised alt - A case study in validated design using CSP - Lowe, G (2011)
In this paper we describe the design and implementation of a generalised alt operator for the Communicating Scala Objects library. The alt operator provides a choice between communications on different channels. Our generalisation removes previous restrictions on the use of alts that prevented both ends of a channel from being used in an alt. The cost of the generalisation is a much more difficult implementation, but one that still gives very acceptable performance. In order to support the design, and greatly increase our confidence in its correctness, we build CSP models corresponding to our design, and use the FDR model checker to analyse them. © 2011 The authors and IOS Press. All rights reserved.